Short-Term Effects of Regulated Deficit Irrigation of 'Rojo Brillante' Persimmon (Dyospyros kaki) - Yield, Fruit Quality and Post-Harvest Performance - Intrigliolo, Diego S.; Bonet, Luis; Ferrer-Talón, Pedro J.; Besada, Cristina; Salvador, Alejandra (2017)
Persimmon trees (Diospyros kaki) belongs to the so-called group of minor fruit tree species. The main persimmon cultivar grown in Spain is ‘Rojo Brillante’, which produces an astringent fruit. This implies the need of deastringency post-harvest treatments prior commercialization. Persimmon growing in Spain is concentrated in an area of water scarcity, but there is no information about tree water needs or responses to deficit irrigation. With this in mind, an experiment was started with the objective to determine tree water needs and yield responses to water restrictions applied during different stages of fruit growth. Moreover the effect of the deficit irrigation period on the level of astringency at harvest and after a deastringency treatment with elevated CO2 were determined. Four irrigation treatments where applied including watering at 100% the estimated tree evapotranspiration during the entire season, and other three treatments where irrigation inputs were severely reduced but only during certain periods (spring, summer or fall). Water deficit, particularly if applied during spring or summer, reduced yield, mainly due to reduced fruit weight. However, water restrictions, particularly when applied late in the season lead to lower fruit firmness than the control. Therefore, this treatment accelerated fruit ripening. None of the deficit irrigation treatments affected the astringency level of the fruit at harvest or after the deastringency treatment.